Feeding selectivity and influence of leaf age of Eucalyptus spp. for Thyrinteina arnobia (Lepidoptera: geometridae) - Lemos, Raimunda Nonata Santos; Crocomo, Wilson Badadiali; Forti, Luiz Carlos; Wilcken, Carlos Frederico (Pesquisa Agropecuaria Brasileira, 1999)
Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) is considered one of the most serious Eucalyptus pests in Brazil. This work was carried out aiming to study feeding preference of T. arnobia and the influence of leaf age on the host selection, using young and old leaves of Eucalyptus grandis, Eucalyptus camaldulensis, Eucalyptus saligna, Eucalyptus citriodora, Eucalyptus robusta e Eucalyptus cloeziana. Caterpillars fed with E. grandis leaves in previous generation, preferred young leaves of E. grandis and E. cloeziana, while caterpillars fed with E. saligna in previous generation preferred old leaves of E. grandis. The most consumed species was E. grandis, and the caterpillars preferred young leaves than old ones, for all species studied.